Wool shedding and lamb fleece weights: first-cross and backcross Wiltshire–Romney sheep scored at lamb, hogget and two-tooth ages - Sneddon NW; Handcock RC; Corner-Thomas RA; Kenyon PR; Burnham DL; Garrick DJ; Littlejohn MD; Blair HT; Morris ST (Taylor and Francis Group, 2024)
With decreasing wool values, interest is increasing regarding shedding sheep. To investigate this, two long-term studies introducing Wiltshire genes into Romney flocks were initiated. Data from these two studies provide phenotypic relationships between a range of shedding scores at different ages. The data included shedding scores (on a 0–5 scale) repeated on lambs (∼5 months), hoggets (∼14–18 months) and two-tooths (∼27 months), and lamb fleece weights. Positive relationships between shedding scores on the same animals were observed. Lamb fleece weight was negatively correlated with all shedding scores. Lamb shedding score in February had a correlation of 0.54 (P < 0.001) with the February score as a hogget at Riverside farm. Scoring wool shedding is a laborious activity requiring individual animals to be scored in the shearing position. Therefore, lamb fleece weight was investigated for its relationship with shedding scores, as a potentially easier alternative. Lamb fleece weight had a greater correlation with February hogget shedding score than with the lamb shedding score (−0.76 vs −0.52, P < 0.001). This study indicated that February scores are an accurate predictor of future shedding phenotypes, and when used in conjunction with fleece weight, are a good predictor of phenotypes expressed at later ages.
Keywords: Wiltshire; Romney; shedding; lamb ﬂeece weight; selection